Web-Based Nutrition and Physical Activity Education Intervention to Ameliorate Cardiometabolic Risks: A Single-Arm and Non-Randomized Feasibility Study - Mohd Ramadan Ab Hamid; Siti Sabariah Buhari; Harrinni Md Noor; Nurul 'Ain Azizan; Norazmir Md Nor (SAGE Publishing, 2023)
Objective: This study aimed to evaluate the feasibility of the D-PATH website to improve dietary and physical activity management for patients with cardiometabolic risk. Methods: A website called D-PATH was developed, consisting of 6 learning units for managing hypertension. A 4-week program was implemented, and a pre- and post-intervention assessment was conducted to measure acceptability and changes in knowledge, attitude and practice, dietary intake, physical activity, and anthropometric status. Results: The D-PATH website was acceptable in terms of understandability, actionability and cognitive load. Knowledge, attitude and practice, and physical activity levels were improved, but no changes were noted for dietary intake and blood pressure level. Conclusion: The D-PATH website was accepted and feasible for the intervention study. This study has shed light on using the website to promote behavioral change in patients with cardiometabolic risks.